Extraskeletal Myxoid Chondrosarcoma of the Midfoot Presenting as Charcot Arthropathy: A Case Report. Issue 4 (October 2019) - Wilson, John T.; Pitts, Charles; Hess, Matthew; Phillips, Sierra G.; Siegal, Gene P.; Johnson, Michael D.
Abstract : Case: Extraskeletal myxoid chondrosarcoma (EMC) is a rare soft tissue malignancy that very seldomly presents in the foot or ankle and as a result is not commonly in the differential of patients presenting with foot pain. We cite a case of EMC presenting in the atypical location of the midfoot. Because of its location and similarities, this tumor was initially misdiagnosed and mistreated by multiple medical providers as midfoot Charcot arthropathy. Conclusions: Neoplastic etiologies, including EMC, should remain in the differential for atypical, refractory foot pain that presents in a manner similar to Charcot foot.